2011
DOI: 10.1080/15287394.2011.590103
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to Environmental Contaminants Detected in Canadian Arctic Human Populations Changes Bone Geometry and Biomechanical Properties in Rat Offspring

Abstract: Arctic inhabitants consume large proportions of fish and marine mammals, and are therefore continuously exposed to levels of environmental toxicants, which may produce adverse health effects. Fetuses and newborns are the most vulnerable groups. The aim of this study was to evaluate changes in bone geometry, mineral density, and biomechanical properties during development following perinatal exposure to a mixture of environmental contaminants corresponding to maternal blood levels in Canadian Arctic human popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…Decreased femur length and cross‐sectional geometry parameters (CSA and perimeters) were observed in developing and adult rats that were exposed to TCDD (Finnilä et al, ; Miettinen et al, ); however, the bone growth impairment was reversible after elimination of TCDD from the body (Miettinen et al, ). Similarly, rat offspring exposed in utero and lactationally to either A1254 (Elabbas et al, ) or a contaminant mixture composed of 14 PCB congeners (Elabbas et al, ) had decreased femur and tibia lengths (Elabbas et al, ) and decreased total and cortical cross‐sectional areas and perimeters on PND 35; these effects disappeared by PND 77 and PND 350 (Elabbas et al, ). The smaller medullary area of the femur mid‐diaphysis in the PCB‐169 group is in accordance with data obtained in adult animals chronically exposed to TCDD (Herlin et al, ; Jämsä et al, ); a relatively small medullary area was also suggested be a sensitive and consistently affected endpoint of AhR‐mediated toxicity (Herlin et al, ; Jämsä et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased femur length and cross‐sectional geometry parameters (CSA and perimeters) were observed in developing and adult rats that were exposed to TCDD (Finnilä et al, ; Miettinen et al, ); however, the bone growth impairment was reversible after elimination of TCDD from the body (Miettinen et al, ). Similarly, rat offspring exposed in utero and lactationally to either A1254 (Elabbas et al, ) or a contaminant mixture composed of 14 PCB congeners (Elabbas et al, ) had decreased femur and tibia lengths (Elabbas et al, ) and decreased total and cortical cross‐sectional areas and perimeters on PND 35; these effects disappeared by PND 77 and PND 350 (Elabbas et al, ). The smaller medullary area of the femur mid‐diaphysis in the PCB‐169 group is in accordance with data obtained in adult animals chronically exposed to TCDD (Herlin et al, ; Jämsä et al, ); a relatively small medullary area was also suggested be a sensitive and consistently affected endpoint of AhR‐mediated toxicity (Herlin et al, ; Jämsä et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Transfer of PCB congeners to mature and developing bone tissue has previously been documented (Jan et al, ; Jan et al, ), and accumulating evidence has demonstrated their ability to modulate bone morphology, development and bone mineral density (Andrews, ; Lind et al, ; Cocchi et al, ; Sonne et al, ). In laboratory rats, alterations in growth and bone tissue homeostasis have been well documented after short‐term or chronic exposure to mixtures of environmental contaminants (Elabbas et al, ), dioxins (Jämsä et al, ; Lind et al, ; Nishimura et al, ) and PCBs (Lind et al, ; Ramajayam et al, ). More specifically, in utero and lactational TCDD exposure affected the bone growth and mechanical strength of wild‐type AhR rats but not dioxin‐resistant rats (Miettinen et al, ; Nishimura et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have explored the impact of the abovementioned pollutants on the neurological health of offspring [52][53][54][55]. Considering the sensitive period of in utero development, studies have focused on developmental outcomes following toxicant exposure.…”
Section: Maternal Brain and Behaviourmentioning
confidence: 99%
“…Exposure to PCBs and environmental organochlorines has been shown to affect bone mineral density in humans (Hodgson et al, 2008) and wild animals including polar bears (Daugaard-Petersen; Sonne et al, 2015), Baltic grey seal (Lind et al, 2003) and freshwater turtle (Ming-Ch'eng Adams et al, 2016). Bone studies in experimental animals reported biochemical and toxicological responses after exposure to TCDD (Herlin et al, 2013;Jämsä et al, 2001;Lind et al, 2009;Nishimura et al, 2009), environmental and commercial mixtures of chemical pollutants (Daugaard-Petersen et al, 2018;Elabbas et al, 2011aElabbas et al, , 2011bRamajayam et al, 2007) or individual PCBs (Brankovič et al, 2017;Gutleb et al, 2010;Lind et al, 2000). In young animals, after in utero and lactational exposure to TCDD, bone growth and mechanical strength were affected in wild-type AhR rats on postnatal day (PND) 40 (Miettinen et al, 2005), and bone mineralization was impaired in mice on PND 21 (Nishimura et al, 2009).…”
Section: Introductionmentioning
confidence: 99%